Attention-Deficit/Hyperactivity Disorder and Outcome from Concussion: Examining Duration of Active Rehabilitation and Clinical Recovery. (2nd November 2022) - Cook, Nathan E.; Teel, Elizabeth; Iverson, Grant L.; Friedman, Deborah; Grilli, Lisa; Gagnon, Isabelle
Abstract: Aims: The objective of this study was to compare recovery time and duration of active rehabilitation following concussion between adolescents with and without attention-deficit/hyperactivity disorder (ADHD). Methods: A retrospective cohort study was conducted among adolescents presenting to a specialty concussion clinic. One-quarter of the eligible episodes of care were selected. The final sample included 540 adolescents (ages 13–17 years, median age 15 years; 49.8% girls), of which 65 (12.0%) had a pre-injury diagnosis of ADHD. Days to recovery and days of active rehabilitation were examined. Results: ADHD was not associated with recovery time (ADHD: median = 49 days, IQR = 25–77; No ADHD: median = 47 days, IQR = 29–85) in univariate (Z = −0.45; p = 0.65) or multivariable analyses (Hazard Ratio: 1.17 (0.85–1.61); χ 2 (1) = 0.95; p = 0.33). The duration of active rehabilitation services received did not differ between youth with ADHD (median = 38.5 days, IQR = 27.5–54.5) and without ADHD (median = 37.5 days, IQR = 18.5–66) in univariate (Z = −0.19; p = 0.85) or multivariable analyses (Hazard Ratio: 1.04 (0.67–1.63); χ 2 (1) = 0.03; p = 0.85). Conclusions: Our findings support accumulating evidence that ADHD, in and of itself, is not a risk factor for longer recovery or worse outcomes following pediatric concussion.